Freshmen's use of library electronic resources and self-efficacy - Micaela Waldman (Information Research: An International Electronic Journal)
To encourage students use of the library, and in particular of its electronic resources, we need to understand what factors encourage students to seek out information in the library setting. Research has shown that self-efficacy influences academic achievement. This paper looks at the role self-efficacy plays in their search for information and use of the library's electronic resources, by surveying a class of freshmen at Baruch College. Their library and computer use were analyzed and correlated with their self-efficacy scores. Through statistical analysis, we found that use of the library correlated to the students' use of the library's electronic resources. We also found out that students who express an interest in learning about the library's electronic resources will be more likely to have higher self-efficacy.